Three new genera of Ptilomerinae (Hemiptera: Heteroptera: Gerridae) from Southeast Asia - Zettel, H. (Zootaxa, 2009)
Celerobates gen. n. is erected and described to hold Rhyacobates imadatei Miyamoto, 1967 (type species). Celerobates imadatei (Miyamoto, 1967) comb. n. is probably endemic to Borneo, where it inhabits the torrents of large streams. Two further new genera are closely related with Ptilomera Amyot & Serville, 1843: Ptilomerella gen. n. is described from the southeast Asian mainland: Ptilomerella akekawati sp. n. (type species) is from southern Thailand (Surat Thani, PhangNga, Phuket); and Ptilomerella anderseni sp. n. is from Myanmar (Kayin State). Archaeoptilomera gen. n. is described from Borneo; Archaeoptilomera derlethi sp. n. (type species) is from East Kalimantan, Indonesia; and Archaeoptilomera kodadai sp. n. is from Sarawak, Malaysia.